Adjective clauses in the -er suffix of occupation definitions in online dictionaries - Erina Andriani; Barli Bram (Studies in English Language and Education, 2022)
Learners’ dictionaries are often intended to assist students with distinct proficiency levels. However, few studies have shown how dictionaries with different intended users were compared. This paper aimed to compare and contrast adjective clauses in -er suffix occupation definitions in two online dictionaries. Data, consisting of 33 occupation words with the suffix -er, such as ‘barber’ and ‘waiter’, were collected from the online Longman Dictionary of Contemporary English (LDOCE) and the online Oxford Advanced Learner’s Dictionary (OALD) using purposive sampling. The data were analysed using syntactic analysis, focusing on the components of adjective clauses. The results showed the head noun of the adjective clauses differed; LDOCE used pronouns most frequently (80.6%), while OALD used noun phrases only (100%). The relative pronoun ‘who’ was used more frequently in LDOCE (48.4%) and ‘whose’ in OALD (62.5%). Transitive verbs were used the most in LDOCE (48.4%), but in OALD, it was linking verbs (57.9%). The additional information that affected the length of the adjective clauses was longer in OALD compared to LDOCE. The study results provide pedagogical implications for English learning-teaching by utilizing online dictionaries. English teachers and learners are encouraged to integrate dictionaries into the learning-teaching activities.